Analisis Semiotika Iklan Smartphone Oppo - Anddina Kholifatul Janah; Melya Puspita; Miftahul Hasanah; Anas Malik (Jurnal Bisnis Kreatif dan Inovatif, 2024)
Abstract. Semiotic analysis of advertising aims to uncover the hidden meanings behind visual and textual elements presented in promotional content. This study explores the semiotic features in smartphone advertising, focusing on Oppo as a case study. This study uses a comparative framework to analyze the similarities and differences between Oppo advertising and competing brands. The analysis is conducted through Charles Sanders Peirce's triadic model, consisting of representamen, object, and interpretant, as well as Roland Barthes' concepts of denotation and connotation. This study identifies symbolic, iconic, and indexical signs used in Oppo advertising to build brand identity and attract target audiences. Key findings reveal how visual elements, color schemes, and slogans emphasize innovation, premium quality, and emotional connection. Comparative insights highlight Oppo's differentiation strategies, such as integrating cultural nuances and leveraging aspirational imagery, to strengthen its market position. The results of this study provide a deeper understanding of how semiotic strategies influence consumer perception and purchasing behavior, as well as provide practical implications for marketers and advertisers. This study bridges the gap between semiotic theory and its application in modern advertising, providing a comprehensive perspective on the power of signs in shaping brand narratives.